2018
DOI: 10.1038/s41598-018-19442-7
|View full text |Cite
|
Sign up to set email alerts
|

Activated forms of astrocytes with higher GLT-1 expression are associated with cognitive normal subjects with Alzheimer pathology in human brain

Abstract: Although the cognitive impairment in Alzheimer’s disease (AD) is believed to be caused by amyloid-β (Aβ) plaques and neurofibrillary tangles (NFTs), several postmortem studies have reported cognitive normal subjects with AD brain pathology. As the mechanism underlying these discrepancies has not been clarified, we focused the neuroprotective role of astrocytes. After examining 47 donated brains, we classified brains into 3 groups, no AD pathology with no dementia (N-N), AD pathology with no dementia (AD-N), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 62 publications
1
80
0
1
Order By: Relevance
“…These studies used AD patient samples and mouse models. In human patient samples, astrocytes are neuroprotective when glutamate transporters are highly expressed [47]. Glutamate transporter expression varies among mouse models of AD and depends on the brain region.…”
Section: Discussionmentioning
confidence: 99%
“…These studies used AD patient samples and mouse models. In human patient samples, astrocytes are neuroprotective when glutamate transporters are highly expressed [47]. Glutamate transporter expression varies among mouse models of AD and depends on the brain region.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction of GLT-1/EAAT2 expression by astrocytes parallels the progression of AD pathology in the human brain (Simpson et al, 2010 ). Recently, it has been proposed that preservation of GLT-1/EAAT2 expression in GFAP+ reactive astrocytes could be a mechanism of resilience against AD neuropathological changes (Kobayashi et al, 2018 ). Other authors have shown a decreased solubility of GLT-1/EAAT2 in the brain of patients with AD, which could potentially impair the re-uptake of synaptic glutamate (Woltjer et al, 2010 ).…”
Section: Functional Consequences Of Astrocyte Reaction In Alzheimer’smentioning
confidence: 99%
“…This reduction of GLT-1 expression in astrocytes results in increased glutamate levels at the synapse, which, by acting on eNMDAR, contributes to the progression of AD pathology in the human brain (Simpson et al, 2010). Additionally, a study performed in postmortem human samples suggests that the preservation of GLT-1 expression in reactive astrocytes could act as a neuroprotective mechanism against AD neuropathological changes (Kobayashi et al, 2018).…”
Section: The Old Man and The Alzheimer's Diseasementioning
confidence: 99%